Pengaruh Sosialisasi Perpajakan, Kesadaran Wajib Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Janiar Sefia Risti; Syaiful (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effect of tax socialization, taxpayer awareness, and tax sanctions on individual taxpayer compliance. This research uses a quantitative research approach. The population in this study consists of individual taxpayers who possess a Taxpayer Identification Number (NPWP), are registered at KPP Pratama Gresik, and operate as entrepreneurs in Gresik Regency. The sampling technique used is purposive sampling, which selects samples based on predetermined criteria. Data were collected through questionnaires distributed to 75 respondents. The data analysis method employed is multiple linear regression analysis using IBM SPSS Statistics 22. The results of this study indicate that tax socialization has a significant effect on taxpayer compliance. Taxpayer awareness also has a significant effect on taxpayer compliance. In addition, tax sanctions have a significant effect on individual taxpayer compliance.